Learning to drive in young adults with language impairment. (October 2016) - Durkin, Kevin; Toseeb, Umar; Pickles, Andrew; Botting, Nicola; Conti-Ramsden, Gina
Highlights: First study of entry into driving by young people with language impairment (LI). Individuals with LI are less likely than peers to have acquired a licence by age 24. Language and independence at 17 contribute to the prediction of holding a licence. Individuals with LI are at no greater risk of traffic violations/accidents. Individuals with LI may benefit from support during the preparation and test phases. Abstract: Language impairment (LI) is a common developmental disorder which affects many aspects of young people's functional skills and engagement with society. Little is known of early driving behaviour in those with this disability. This longitudinal study examines early driving experience in a sample of young adults with LI, compared with a sample of typically developing age-matched peers (AMPs). At age 24 years, significantly fewer participants with LI had acquired a driving licence. A crucial hurdle for those with LI appeared to be the Theory part of the (UK) test. Logistic regression analysis indicated that language ability and a measure of independence at age 17 contributed to the prediction of licence possession at age 24. There was no evidence of differences in traffic violations or accident rates between those with and without LI. There is little evidence that young people with LI are at greater risk on the roads than peers without LI, but some individuals with LI might benefit from support in the course of preparation for driving and in the driving test.